Ecologia comportamental de Crossodactylus schmidti Gallardo, 1961 (Anura, Hylodidae): atividade reprodutiva, comunicação acústica, visual e multimodal - Caldart, Vinícius Matheus (2015)
The communication process has a fundamental role in the life history of organisms, as it assumes a coevolutionary interaction between sender and receiver. The acoustic communication has a key role in the life history of anurans, as it is used to mediate social interactions, influences the risk of predation and parasitism and is directly linked to reproduction and reproductive success. However, species that inhabit acoustically complex environments, such as streams, face an ecological problem inherent of this type of habitat that affects acoustic communication: the noise produced by stream torrents. Remarkably, the visual communication has convergently evolved in several families of diurnal stream frogs and, in addition, some of these species are known to also use visual and acoustic signals associated within multimodal displays. I investigated the geographic distribution, natural history, ecology and behavior of the diurnal stream frog Crossodactylus schmidti (Hylodidae) in southern Brazil, addressing questions relative to the reproductive activity and communication through in situ observations and experiments and through the analysis of collected specimens. Regarding the reproductive activity, I evaluated the temporal patterns of male calling activity and the effect of environmental factors on daily/monthly activity, the temporal patterns of sexual maturity, the "size x fecundity" relationships and the reproductive investment of males and females. Regarding communication, I investigated the selective pressures that influence the structure of signals (adaptations) and the use of strategies in communication (plasticity), described the acoustic, visual and multimodal repertoire, the microhabitat used to emission of visual/multimodal displays, and investigated relations between "acoustic signal x ambient noise" and the interaction between parasitic flies and calling male frogs. Communication in C. schmidti is complex and involves a wide repertoire of acoustic, visual and multimodal signals. Males have continuous calling activity throughout the year, with varying effects of environmental factors: the accumulated precipitation and air temperature affected the monthly calling activity, while the light intensity and air temperature affected the daily activity. The pattern of reproductive activity of C. schmidti in southern Brazil fits into the continuous type, with the presence of sexually mature individuals of both sexes throughout the year, which suggests strong intrasexual competition and that the species’ mating system is a "resource defense polygyny". Some of the notes that compose the species multi-note advertisement call showed negative signal-to-noise ratio for calls of all analyzed males. Given the masking effect of the ambient noise on the acoustic signal transmission, C. schmidti presents acoustic adaptations (e.g., multi-note call, visual communication), and plasticity in acoustic traits (e.g., dominant frequency modulation) related to sudden/temporary changes in ambient noise. Flies of the genera Corethrella were indeed attracted to frog calls, while Forcipomyia and Uranotaenia flies were not; this pattern was reinforced by the lack of difference in the treatment with a white noise and adjacent silent traps. However, the pattern of abundance of Corethrella is much lower when compared to tropical areas. Studying a singular species as C. schmidti provides a valuable opportunity to understand the evolution of temporal strategies of reproduction, adaptations and behavioral plasticity related to the communication of diurnal stream frogs.